The Effectiveness of Prezi Web-Based Teaching Media to Improve Nursing Students’ Comprehension - Yanto, Arief; Warsono, Warsono (South East Asia Nursing Research, 2020)
The process of nursing education requires a teaching media which straightforward to be comprehend. Inappropriate determining the teaching media leads nursing students face difficulties to receive an adequate course’s guidance from the educators. Prezi is a web-based presentation program which comprehensively integrates text, picture, animation, video and audio into one presentation file. This study is aimed to determine the effectiveness of Prezi web-based teaching media on improving nursing students’ comprehension. A quantitative-experimental method with pretest-posttest control group design was applied. A total of 176 nursing students were recruited by using non probability sampling approach. The study indicated Prezi web-based teaching media showed significant result on improving students’ knowledge. The determination of Prezi web-based program is suggested to improve students’ comprehension in nursing education.